2014
DOI: 10.1155/2014/728572
|View full text |Cite
|
Sign up to set email alerts
|

A Gastrointestinal Electrical Stimulation System Based on Transcutaneous Power Transmission Technology

Abstract: Electrical stimulation has been suggested as a possible treatment for various functional gastrointestinal disorders (FGID). This paper presents a transcutaneous power supplied implantable electrical stimulation system. This technology solves the problem of supplying extended power to an implanted electrical stimulator. After implantation, the stimulation parameters can be reprogrammed by the external controller and then transmitted to the implanted stimulator. This would enable parametric studies to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Other works adopting functional electrical stimulation have also been shown as a potential treatment, including lower esophageal sphincter stimulation for GERD [ 4 ], gastric stimulation for obesity [ 5 ], intestinal stimulation for post-operative ileus management [ 6 ], and colon stimulation to control the movement of solid content using a multichannel stimulator [ 7 ]. Nonetheless, the clinical effectiveness and applicability of implantable GI electrical stimulation is somehow limited by the capabilities of existing implantable GI stimulators, including (1) limited programmability: it has been shown that a wide range of parameters (e.g., 0.2–100 ms, 10–50 mA, and 3–1670 Hz) can be used to induce GI contraction [ 8 ], but no existing implantable stimulator can produce stimulus with >2 ms pulse width and stimulation with long pulse width might create tissue damage [ 9 , 10 ], (2) no GI implant is capable of sensing GI motility [ 11 , 12 , 13 ], and (3) bulky device size which increases surgical invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Other works adopting functional electrical stimulation have also been shown as a potential treatment, including lower esophageal sphincter stimulation for GERD [ 4 ], gastric stimulation for obesity [ 5 ], intestinal stimulation for post-operative ileus management [ 6 ], and colon stimulation to control the movement of solid content using a multichannel stimulator [ 7 ]. Nonetheless, the clinical effectiveness and applicability of implantable GI electrical stimulation is somehow limited by the capabilities of existing implantable GI stimulators, including (1) limited programmability: it has been shown that a wide range of parameters (e.g., 0.2–100 ms, 10–50 mA, and 3–1670 Hz) can be used to induce GI contraction [ 8 ], but no existing implantable stimulator can produce stimulus with >2 ms pulse width and stimulation with long pulse width might create tissue damage [ 9 , 10 ], (2) no GI implant is capable of sensing GI motility [ 11 , 12 , 13 ], and (3) bulky device size which increases surgical invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a first individual motility evaluation would take place in a more physiological environment. Together with recent advances in wireless GI device developments [33, 35, 36], even the scenario of robotic placement of multiple theranostic devices distributed along the GI tract appears reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…The first study regarding the CES to modulate colonic motility was performed by Hughes et al [37]. Since then, many researchers employed short-pulse CES in canine descending colon or pig cecum [20,21,38]. Researchers also applied long-pulse CES to stimulate the colon of human or animals [39].…”
Section: Discussionmentioning
confidence: 99%